Effective strategies for coordinated rehabilitation - L. Shuranova; J. Vacková; K. Rimárová; A. Hryshchuk (Medičnì Perspektivi)
Rehabilitation of stroke patients is a complex process that requires coordination between healthcare professionals, patients and their families. This study aims to develop strategies to optimize coordinated care and rehabilitation in order to improve patients' quality of life and facilitate their return to normal life. The main objective is to examine the implementation of coordinated care and rehabilitation before, during and after hospital discharge. The study was conducted within the framework of the project GAJU 066/2022/S, approved by the Ethics Commission (number 6/2022). A qualitative approach was used, with semi-structured interviews with healthcare professionals involved in the rehabilitation of patients after stroke as the main method of data collection. The study involved 143 professionals from different hospitals, including doctors, physiotherapists, occupational therapists, psychologists, social workers and nurses. The data were analysed using ATLAS.ti software and different coding strategies [1]. Based on the information obtained, a SWOT analysis was conducted, the results of which were used to propose process optimization. It helped to identify key strengths, weaknesses, opportunities and threats to coordinated rehabilitation. The results indicate the need to improve cooperation between professionals and increase the availability of coordinated rehabilitation services. Key challenges include insufficient support and awareness of patients and their families, limited access to home-based rehabilitation services, and insufficient coordination between health and social service providers. Recommended strategies include improving interprofessional communication, expanding access to home-based services, increasing financial support, improving education of patients and their families, and introducing a system for monitoring the quality of services provided.